PEMBELAJARAN PKn DENGAN PENDEKATAN COOPERATIVE LEARNING TIPE GROUP INVESTIGATION DI KELAS IV SEKOLAH DASAR - bakar, yanti; Reinita, Reinita; Mansurdin, Mansurdin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
ABSTRACTThe purpose of this study was to describe the improvement of student learning outcomes in Civics Learning with Cooperative Learning Approach Type of Group Investigation (GI) in class IV SDN 08 Kampung Pondok Padang. The type of research used is Class Action Research using qualitative and quantitative approaches. The research subjects were teachers (practitioners) and 18 students. The results showed an increase in terms of a) RPP cycle I was 82.14% and cycle II 92.85%, b) Implementation in the aspect of the teacher cycle I was 84.37% and cycle II 96.87% while the implementation in the aspect of students cycle I is 81.25% and cycle II is 93.75%, c) Student learning outcomes in cycle I are 71.53 and cycle II 86.07. It was concluded that the Cooperative Learning Approach Type of Group Investigation (GI) can improve student learning outcomes in Civics Education in Elementary Schools.                                  Keywords: Civics Learning Outcomes; Group Investigation